2009
DOI: 10.1063/1.3216805
|View full text |Cite
|
Sign up to set email alerts
|

Locally resonant phononic woodpile: A wide band anomalous underwater acoustic absorbing material

Abstract: To meet the demand of modern acoustic absorbing material for which acoustic absorbing frequency region can be readily tailored, we introduced woodpile structure into locally resonant phononic crystal ͑LRPC͒ and fabricated an underwater acoustic absorbing material, which is called locally resonant phononic woodpile ͑LRPW͒. Experimental results show that LRPW has a strong capability of absorbing sound in a wide frequency range. Further theoretical research revealed that LRPC units and woodpile structure in LRPW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 27 publications
(24 reference statements)
1
50
0
1
Order By: Relevance
“…Thus, phononic glass with greater porosity can more easily achieve broadband absorption because of cooperation from the interpenetrating network. This influence of porosity of phononic glass on its acoustic performance is similar to the influence of thickness previously reported [8,9], where the onset frequencies shifted down as the sample thickness increased. This change with thickness can be explained by local resonance theory.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Thus, phononic glass with greater porosity can more easily achieve broadband absorption because of cooperation from the interpenetrating network. This influence of porosity of phononic glass on its acoustic performance is similar to the influence of thickness previously reported [8,9], where the onset frequencies shifted down as the sample thickness increased. This change with thickness can be explained by local resonance theory.…”
Section: Resultssupporting
confidence: 68%
“…In LRSMs, locally resonant absorption coincides with viscoelastic deformation [11][12][13][14][15][16][17][18]. The sound-absorption region in LRPCs was first found using the multiple-scattering approach; these results showed that a conversion from longitudinal mode to transverse mode near the locally resonant frequencies effectively enhanced the anechoic performance of these materials [7,14].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This unique property gives rise to a variety of novel phenomena and applications in the area of sound and vibration . These intriguing features include low-frequency band gaps [5,[7][8][9][10][11], low-frequency sound shielding [12][13][14][15], low-frequency sound absorption [16][17][18][19][20][21], negative dynamic density or elastic modulus [2,[22][23][24][25], and even negative refraction [26,27]. On account of their negative dynamic properties and negative refraction behaviours which natural materials do not possess, LRSMs are also designated as acoustic metamaterials [23,26,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%